Educational Marketing Management in Attracting New Students - Ramdani Indri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
Educational marketing strategy management serves as a crucial instrument in responding to the dynamic competition among educational institutions, particularly in the context of increasing student enrollment. This study aims to explore the implementation of marketing strategies carried out by SMP Plus Miftahul Falah Cikalong, focusing on market segmentation, target setting, institutional positioning, and the application of educational promotional mix strategies. A descriptive qualitative method was employed, with data collected through field observations, in-depth interviews, and documentation. The analytical process follows Miles and Huberman’s interactive model, which involves three stages: data reduction, data display, and conclusion drawing. The subjects involved in this inquiry include the principal, teachers, student admission committee members, and new students to represent the user perspective. Findings reveal that the institution has systematically implemented a marketing strategy aligned with the values and needs of the local community. Contributing factors to the effectiveness of the promotion include the institution's pesantren-based image, the quality of human resources, and adequate infrastructure. Conversely, limited promotional budgets and the digital literacy gap within the marketing team remain significant obstacles to expanding promotional outreach. These findings suggest that the success of educational marketing strategies is not solely dependent on the promotional content but also on the institution's ability to construct a relevant image and establish effective communication with the public. This work is expected to serve as a conceptual reference for Islamic educational institutions in formulating more adaptive and contextual promotion strategies.